UMP associates share stories in fighting COVID 19 - Nor Salwana, Mohammad Idris (2021)
PEKAN, 17 September 2021 - The current pandemic requires us to continue to abide by every standard operating procedure (SOP) set to free the country from being colonised by silent enemies and it is a highly demanded struggle from the people right now.